Topography changes and thermal distribution at the Kelud crater after the 2014 Plinian eruption - Wahyudi Wahyudi; Ari Setiawan; Heriansyah Putra; Herlan Darmawan; Imam Suyanto; Irwan Meilano; Irzaman irzaman; Maria Evita; Mitra Djamal; Moh Yasin; Nina Siti Aminah; Perdinan Perdinan; Retna Apsari; Wahyu Srigutomo; Wiwit Suryanto (Faculty of Geography, Universitas Gadjah Mada, 2020)
Topography of a volcano crater can change due to endogenic processes such as deformation or eruption, or surface processes. Erosion and deposition are surface processes that may occur and gradually change the slope of the inner volcano crater. Here, we investigated erosion and deposition processes that occurred in the Kelud crater after the 2014 plinian eruption. We used high-resolution Digital Elevation Models (DEMs) and orthomosaic images derived by drone photogrammetry that acquired between September 2018 and July 2019. We obtained hundreds of aerial images which were reconstructed to obtain 3D models of Kelud’s crater by using Structure from Motion (SfM) technique. Results show erosions at alluvial fans that dominantly located at the east valleys of Kelud crater. The erosion removed the volcanic materials up to -5 m which transported and deposited close to the vicinity of the Kelud crater. The deposition process causes the increase of the Kelud crater lake up to 3 m. Moreover, we also mapped the thermal distribution of the Kelud crater lake by using low cost thermal camera. Our thermal investigation is able to identify some hotspots at the vicinity of the Kelud crater lake with range temperature of 43.7°C – 55.3°C, while the average apparent temperature of the Kelud crater lake is 29°C. This high temperature area may indicate underwater active fractures that continuously release volcanic gasses which leads to convection heat transfer through Kelud’s water lake.